Conditioned Medium of Human Amniotic Epithelial Cells Alleviates Experimental Allergic Conjunctivitis Mainly by IL-1ra and IL-10 - Wu, Binxin; Gao, Furong; Lin, Jianhua; Lu, Lixia; Xu, Huiming; Xu, Guo-Tong (Frontiers in Immunology, 2021)
Allergic conjunctivitis is the most prevalent form of mucosal allergy and the conditioned medium (CM) from mesenchymal stem cells have been reported to attenuate some allergic diseases. However, the therapeutic effects of CM from different tissue stem cells (TSC-CM) on allergic diseases have not been tested. Here, we studied the effects of topical administration different human TSC-CM on experimental AC (EAC) mice. Only human amniotic epithelial cell-CM (AECM) significantly attenuated allergic eye symptoms, reduced the infiltration of immune cells and the levels of local inflammatory factors in the conjunctiva compared to EAC mice. In addition, AECM treatment decreased IgE release, histamine production and the hyperpermeability of conjunctival vessels. Protein chip assays revealed that the levels of anti-inflammatory factors, interleukin-1 receptor antagonist (IL-1ra) and IL-10, were higher in AECM compared to other TSC-CM. Furthermore, the antiallergic effects of AECM on EAC mice were abrogated when neutralized with IL-1ra or IL-10 antibody and the similar phenomena was for the activation and function of B cells and mast cells. Together, the present study demonstrated that AECM alleviates EAC symptoms by multiple antiallergic mechanisms mainly via IL-1ra and IL-10. Such topical AECM therapy may represent a novel and feasible strategy for treating allergic conjunctivitis.